"You're telling me!" The prevalence and predictors of pronoun reversals in children with autism spectrum disorders and typical development. (July 2016) - Naigles, Letitia R.; Cheng, Michelle; Xu Rattanasone, Nan; Tek, Saime; Khetrapal, Neha; Fein, Deborah; Demuth, Katherine
Highlights: The rate of pronoun reversal in children with ASD is under 10%. Children with ASD nonetheless produced more reversals than TD children. Higher early language and joint attention scores predicted fewer reversals. Reversals occur when language and social abilities develop asynchronously. Abstract: Social and linguistic explanations have been proposed for pronoun reversals in young typically developing (TD) children and those with autism spectrum disorders (ASD). The current study breaks new ground in investigating both explanations, comparing 18 TD toddlers and 15 children with ASD at similar language levels. Spontaneous speech was sampled every four months for six visits. Vocabulary and joint attention were also measured. Both groups produced pronoun reversals at low rates. The ASD group produced somewhat more reversals than the TD group, overall and at multiple visits. In the ASD group, early language and joint attention scores contributed significantly and independently to the incidence of reversal. Both linguistic and social factors seem implicated; moreover, reversals seem to occur when children's language and social abilities develop asynchronously. These findings can help clinicians devise both linguistic and social interventions for the relevant children.